Peluang Biomarker Saliva sebagai Skrining Prediabetes untuk Pencegahan Diabetes Melitus Tipe 2: Literatur Review - Mira Sri Gumilar; Andre Wilia Putra (Jurnal Sehat Mandiri, 2024)
Prediabetes is characterized by elevated blood glucose levels that have not yet reached the threshold for diabetes but are above normal limits. The prediabetes period is a critical window for intervention. Blood sample screening methods are effective but invasive, limiting their widespread use. A non-invasive alternative for glucose testing, such as saliva-based tests, is needed. Saliva-based tests offer ease of use, accessibility, and convenience, making them suitable for broader community screening. This study aims to explore a literature review on prediabetes screening using saliva tests. Research articles were searched using the Google Scholar search engine with keywords “saliva biomarkers”, “saliva for diagnostic test”, and “non-invasive test for diabetes”. The identification was conducted on research articles published between 2014 and 2024. This study employs a qualitative approach in reviewing journal articles on the use of saliva as a test sample for prediabetes screening. The study assesses the potential, challenges, and identification of suitable biomarkers for saliva-based prediabetes screening. The review of the journals shows that saliva has potential as a non-invasively obtained sample for prediabetes screening. The use of saliva samples offers several advantages over blood samples. The research conclusion is that saliva has become an innovative biomarker as a non-invasive tool for screening prediabetes such as levels of glucose, amylase, cortisol, inflammatory markers such as CRP and cytokines, and adipocytokines.